The Role and Impact of Digital Platforms on Customer Engagement and Loyalty in the Services Sector - Kurhasku-Hoti, Edisona; Rrustemi, Visar (Journal of Ecohumanism, 2025)
Digital marketing is a key component of contemporary business strategies, especially in the service sector, where competition and customer demands are changing rapidly. This study examines the importance and effectiveness of digital marketing techniques in service sector businesses in Kosovo, analyzing the benefits, challenges, and approaches used by companies to improve customer interaction. Primary and secondary data were used to conduct the research. Primary data were collected through a structured questionnaire with 101 service sector businesses, while secondary data were obtained from a review of existing literature. The results show that over 84.2% of businesses use digital marketing to maintain an active presence in the market, while the social networks of the Meta group (Facebook and Instagram) remain the most preferred platforms. The main challenges include adapting to new technologies and providing quality content. The study highlights that, to compete effectively, businesses need to invest in specialized resources and adapt their digital strategies to customer needs. These findings contribute to the existing literature, providing a perspective on digital marketing in a transition economy.